Talus Fractures: All I need to know. Issue 11 (November 2021) - Al-Jabri, Talal; Muthian, Senthil; Wong, Ken; Charalambides, Charalambos
Abstract: Talus fractures result following high energy trauma and can lead to significant functional impairment. The complex morphology of the talus, it's multiple articulations and tenuous blood supply translate into significant challenges that must be overcome to achieve the best possible outcomes. Despite advances made in their management, they continue to have high complication rates. Nonetheless, restoration of normal alignment will optimise outcomes. In this article, we report on the epidemiology, anatomy, classification, patient evaluation and current evidence for the management of talus fractures.